Analisis Sistem Pengendalian Internal dalam Pengelolaan Piutang Pada HARRIS Hotel & Conventions Gubeng - Enjelly Talitha Callista; Sari Andayani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research was conducted to analyze internal control in the management of receivables at HARRIS Hotel & Conventions Gubeng. The purpose of this study was to determine the internal control system in managing accounts receivable at HARRIS Hotel & Conventions Gubeng. The research was conducted using a qualitative descriptive approach method which includes data collection, data reduction, presentation and findings. The application of the internal control system in the management of accounts receivable by HARRIS Hotel & Conventions Gubeng has been running well. Proven by the application of ethical standards and clear policies and applying principles in the form of guidelines in carrying out work every day, good information and communication, credit sales policies and holding regular evaluations every month to discuss problems regarding accounts receivable. This greatly supports internal control of accounts receivable management to run effectively.